Kenali loghat Terengganu - Sharif Putera, 1943- (Kuala Terengganu : Sharif Kreatif, 2013)
Malay dialects in Terengganu, Malaysia.
In Malay.
Keywords: Malay language -- Dialects -- Malaysia -- Terengganu